The externalisation of European refugee protection: A legal, practical and political assessment of current proposals - Steffen Angenendt; Nadine Biehler; Raphael Bossong; David Kipp; Anne Koch (Stiftung Wissenschaft und Politik (SWP), 2024)
In many European countries, the number of asylum applications continues to rise, as does the appeal of right-wing populist parties. In response, initiatives such as the British government's Rwanda Plan and the Italian government's agreement with Albania aim to significantly reduce the number of arrivals by transferring asylum procedures and refugee protection to third countries. It is worth noting that although similar proposals in the past have never progressed beyond the idea stage, concrete implementation procedures are currently under discussion for Rwanda and Albania. However, there are several legal and normative concerns as well as practical challenges that need to be carefully considered. These approaches would fundamentally jeopardise international refugee protection and harm vital foreign policy interests as well as the credibility of the development cooperation of Germany and the European Union (EU).
Keywords: 320; European refugee protection; asylum applications; Pacific Solution; Rwanda Plan; agreement with Albania; Germany; European Union (EU); Refugee Convention; European Convention on Human Rights (ECHR)